The Role of Civil Aviation in the National Economy of Karakalpakstan in the 1970s: Analysis of Archival Documents - Qitaybekov Azizbek Kenesbek o’g’li (TARIXIY TADQIQOTLAR, 2026)
The article analyzes the development of civil aviation in Uzbekistan, particularly in Karakalpakstan, during the 1960s–1970s, and its multifunctional role in the national economy. Based on statistical data, it highlights the wide use of aviation in agriculture, geology, oil and gas exploration, medical services, postal communication, and passenger transportation. The findings demonstrate the crucial role of civil aviation in regional economic development.